The benefit of Silybum marianum in ethanol-induced reprotoxicity of male Wistar rat - Amina Talbi; Kamel Khelili; Feriel Remita; Cherif Abdennour (Universidade de São Paulo, 2022)
Abstract This study investigates the toxic effects of ethanol (Eth) on the reproductive system of male rats and the possible protective role of Silybum marianum seeds-infused solution (SMI) over six consecutive weeks of administration. Animals were divided into the following groups: control, SMI positive control (200 mg/kg/day), Eth1 (1 g/kg/day), Eth2 (2 g/kg/day), Eth1+SMI, and Eth2+SMI. Plasma testosterone concentration, epididymal spermatozoa biology, and testicular and epididymal MDA, GSH and GPx levels were evaluated. The results indicated a significant decrease in testis and epididymis weight, testosterone level, sperm concentration, sperm vitality and sperm motility (total motility, progressive motility, curvilinear velocity, straight-line velocity, velocity average path, beat cross frequency, and lateral head displacement) in both Eth1 and Eth2 compared to the control groups and the combined-treatment groups (Eth1+SMI and Eth2+SMI). Furthermore, results showed a significant elevation in MDA concentration with a significant decrease of testicular and epididymal GSH concentration and GPx activity in theEth1 and Eth2 groups compared to the combined-treatment groups. The administration of SMI succeeded in improving the parameters cited above in the combined-treatment groups compared to the Eth1 and Eth2 groups, and bring them to the levels seen in the control groups. To conclude, SMI has clearly protected reproductive indices against ethanol-induced reprotoxicity in male rats